Assessment of In Vitro and In Vivo Bioremediation Potentials of Orally Supplemented Free and Microencapsulated Lactobacillus acidophilus KLDS Strains to Mitigate the Chronic Lead Toxicity - Muhammad, Zafarullah; Ramzan, Rabia; Zhang, Ruifen; Zhao, Dong; Gul, Mehak; Dong, Lihong; Zhang, Mingwei (Frontiers in Bioengineering and Biotechnology, 2021)
Lead (Pb) is a pestilent and relatively non-biodegradable heavy metal with severe health effects by inducing inflammation and oxidative stress in animal and human tissues. Due to its significant tolerance and capability to bind Pb (430mg/L) and thermodynamic fitness to sequester Pb in Freundlich model (R2 = 0.98421) in vitro, Lactobacillus acidophilus KLDS1.1003 was selected for further in vivo study both in free and maize resistant starch (MRS) based microencapsulated forms to assess its bioremediation aptitude against chronic Pb lethality. Orally administered free and microencapsulated KLDS 1.1003 provided significant protection by reducing Pb levels in the blood (127.92±5.220 µg/L and 101.47±4.142 µg/L), kidneys (19.86±0.810 µg/g and 18.02±0.735 µg/g) and liver (7.27±0.296 µg/g and 6.42±0.262 µg/g). MRS-microencapsulated KLDS 1.0344 improved the antioxidant index and inhibited changes in blood and serum enzyme concentrations and relieved the Pb-induced renal and hepatic pathological damages. SEM and EDS microscopy showed that the Pb covered the surfaces of cells and, it was chiefly bound due to the involvement of the carbon and oxygen elements. Similarly, FTIR showed that the amino and amide, phosphoryl, carboxyl and hydroxyl functional groups of bacteria and MRS were mainly involved in Pb biosorption. Based on these findings, free and microencapsulated L. acidophilus KLDS 1.0344 could be considered as a potential dietetic stratagem in alleviating the chronic Pb toxicity.